NEW RECORD OF Chirixalus trilaksonoi (RIYANTO & KURNIATI, 2014) IN JATILAWANG, BANYUMAS, CENTRAL JAVA: UPDATED INSIGHTS FROM MORPHOLOGICAL AND VOCAL CHARACTERIZATION - Hafizh Aulia Khairy Rakananda; Fakhri Fauzan; Quraisy Zakky; Amir Hamidy; Ramadhan (Treubia, 2025)
Genus Chirixalus is a group of small tree frogs within the family Rhacophoridae, distributed across Asia, including northeastern India, southern China, mainland Southeast Asia, and islands such as Sumatra and Java in Indonesia. Ongoing taxonomic research continues to uncover new species within this genus. With the assistance of citizen science, the discovery of new species and the documentation of species’ geographic distribution have been greatly supported, expanding our knowledge of biodiversity and conservation processes. In our study, we recorded the tree frog genus Chirixalus from Jatilawang District, Banyumas Regency, Central Java. Based on our examination of morphological traits and call characteristics, these specimens resemble Chirixalus trilaksonoi. This finding represents the first record extending the known distribution range of Chirixalus trilaksonoi into Central Java. Variation in dorsal morphology and vocal characteristics is the most notable difference observed in this study. This finding can assist field researchers, and citizen scientists particularly those working in taxonomy. Further research and intensive surveys are needed to evaluate its conservation status and enhance our understanding of its taxonomic classification.